Redistributing central bank profits & losses across the eurosystem: The eurosystem's monetary income - Sergio Cesaratto; Eladio Febrero; George Pantelopoulos (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2024)
National Central Banks (NCBs) of the Eurosystem pool profits and losses related to monetary policy operations to form the Eurosystem's so-called 'monetary income'. This is then redistributed - i.e. allocated - among NCBs according to respective capital keys (the participation shares of each NCB to the ECB's capital). Monetary income has relevance for current debates such as that concerning the high fiscal costs of an ample reserve regime as a result of the abundant reserves banks hold in the deposit facility of their respective NCBs. These costs are in fact redistributed through the allocation of monetary income. Nonetheless, exactly how monetary income is pooled and subsequently allocated between Eurosystem NCBs remains rather enigmatic. The aim of this paper is to explore how monetary income is both pooled and allocated. This seems a useful task beyond the aforementioned debate to dissipate other puzzling issues like the costs of TARGET2 imbalances. A more detailed dissemination from the relevant authorities as to the process by which profits/losses are pooled and subsequently allocated is however in our view warranted.
Keywords: 330